Pengaruh Beban Kerja, Kompensasi Dan Motivasi Terhadap Turnover Intention Dengan Stres Kerja Sebagai Variabel Mediasi (Studi pada Perusahaan Leasing PT.X Cabang Pemalang Pos Comal) - Oktafiani, Mutiara; Pantawis, Setyo (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research aims to analyze the influence of workload, compensation and motivation on turnover intention through work stress. The research sample was 64 employees of leasing company PT.X Pemalang Pos Comal Branch, using saturated sampling techniques. Saturated sampling is a sampling technique when all members of the population are used as samples. This sample is a form of probability sampling. Probability sampling is a sampling technique that does not give each element or member of the population the same chance or opportunity to be selected as a sample. This research uses saturated sampling because the population is 64 people, so all members of the population are used as the research sample. The research results show that workload has an insignificant negative effect on turnover intention. Compensation has a negative and significant effect on turnover intention. Motivation has a positive and significant effect on turnover intention. Workload has a positive and significant effect on work stress. Compensation has a positive and significant effect on work stress. Motivation has a positive and significant effect on work stress. Job stress has a positive and significant effect on turnover intention. Workload, compensation and motivation have a positive and significant effect on turnover intention which is mediated by work stress